2017
DOI: 10.1155/2017/2506946
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sorghum Varieties under Variable Rainfall in Central Tanzania

Abstract: Rainfall variability has a significant impact on crop production with manifestations in frequent crop failure in semiarid areas. This study used the parameterized APSIM crop model to investigate how rainfall variability may affect yields of improved sorghum varieties based on long-term historical rainfall and projected climate. Analyses of historical rainfall indicate a mix of nonsignificant and significant trends on the onset, cessation, and length of the growing season. The study confirmed that rainfall vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
5
13
0
1
Order By: Relevance
“…For sorghum, our results showed that the climatic variables were responsible for 70% of the variation in its yield. This finding is in agreement with several studies, which revealed that climatic variables are the most important factors affecting sorghum yield, particularly rainfall [65,66]. Indeed, our model showed that an increase in rainfall amount by 1 mm led to an increase in sorghum yield by 0.11 kg ha −1 .…”
Section: Discussionsupporting
confidence: 93%
“…For sorghum, our results showed that the climatic variables were responsible for 70% of the variation in its yield. This finding is in agreement with several studies, which revealed that climatic variables are the most important factors affecting sorghum yield, particularly rainfall [65,66]. Indeed, our model showed that an increase in rainfall amount by 1 mm led to an increase in sorghum yield by 0.11 kg ha −1 .…”
Section: Discussionsupporting
confidence: 93%
“…The trial was located in a semi-arid climate with a 30-year annual rainfall average of 635 mm (cropping season average of 425 mm) with a unimodal pattern with most rainfall between December and April and a dry period of 6-7 months (Shemsanga et al, 2016) (Figure 1A). Long-term historic (1988Long-term historic ( -2018 rainfall estimates for Manyusi village were downloaded from the Early Warning eXplorer (EWX) Lite time series database and web-based mapping tool (United States Geological Survey, 2020), and are similar to but slightly higher than average annual rainfall for the Dodoma region (589 mm) (Msongaleli et al, 2017).…”
Section: Study Sitementioning
confidence: 99%
“…However, rather than simply the amount of rainfall being significant, rainfall variability during the growing season may be more important. For example, Msongaleli et al [4], using the Agricultural Production Systems Simulator, APSIM [28] model, showed that the length and timing of dry spells during the growing season determined sorghum grain yields in semiarid central Tanzania. Our field experiment and AquaCrop-simulated grain yield results are somewhat contradictory in this respect, with the field experiment grain yield for 2012 being greater than that for 2011, while AquaCrop-simulated grain yields showed the opposite result.…”
Section: Discussionmentioning
confidence: 99%
“…The impact is particularly great for rainfed agricultural systems such as in SSA, where rainfall anomalies causes crop failure and food insecurity [2]. Climate change projections for SSA indicate increases in temperature and a reduction, but increased variability, in rainfall, which will have important negative implications for agriculture and livelihoods [3,4].…”
Section: Introductionmentioning
confidence: 99%